SINGLE-INDUSTRY TOWNS FROM THE PERSPECTIVE OF A SYSTEM ECONOMIC ORGANIZATION AND A RESOURCE THEORY OF CRISES OF ECONOMIC AND SOCIAL SYSTEMS - S. E. Kovan; K. A. Beresin (Стратегические решения и риск-менеджмент, 2014)
The approaches of the resource theory of crises and contingency plan administration have been developed in respect of town-forming organizations of non-diversified centers of population. The introduced economic models let identify and substantiate the emergence of contradictions among economic and social systems, connected by joint activities, in single-industry towns. These problems are expected to be solved through the development of corporate legislation, where it is necessary to settle issues of interdependence, partnership and responsibility not only of legal entities, but also of business groups.